Case Report: Renal relapse after heart transplantation, induction, and autologous stem cell transplantation in a patient with AL amyloidosis with exclusive cardiac involvement - Puertas, Borja; Rey-Búa, Beatriz; Eiros, Rocío; Martín-Arribas, Alberto; Montero-Mateos, Enrique; Hernández-Sánchez, Alberto; Gómez-Úbeda, Sandra; Alejo-Alonso, Elena; Martín-López, Ana A.; Antúnez, Patricia; Villacorta-Argüelles, Eduardo; Gallego-Delgado, María; et al. (Frontiers in Hematology, 2022)
There is no recommendation on what salvage therapy is optimal in the solid organ recipient with AL amyloidosis, such as a heart transplant. With this case, we illustrate how treatment with daratumumab may be effective and safe in a patient with AL amyloidosis with renal involvement at the relapse after heart transplantation and autologous stem cell transplantation.